Soluble galectin-3 is a strong, colonic epithelial-cell-derived, lamina propria fibroblast-stimulating factor. Issue 1 (18th May 2006) - Lippert, E; Falk, W; Bataille, F; Kaehne, T; Naumann, M; Goeke, M; Herfarth, H; Schoelmerich, J; Rogler, G
Abstract : Background: Colonic lamina propria fibroblasts (CLPFs) play an important role in the pathogenesis of fibrosis and strictures in Crohn's disease. Aim: To identify colonic epithelial cell (CEC)-derived factors that activate CLPFs. Methods: Primary human CECs and CLPFs were isolated from control mucosa and interleukin 8 (IL8) of CLPF cultures was quantified by ELISA. Activation of nuclear factor κB (NF-κB) was shown, and translocation of NF-κB was inhibited by a dominant-negative IκB-expressing adenovirus. The major CLPF-activating and IL8 inducing protein was purified using fast-performance liquid chromatography (HiPrep 16/60 Sephacryl S-200 High Resolution Column) and sodium dodecyl sulphate gel electrophoresis. Results: A considerable increase in IL8 secretion by CLPFs cultured in CEC-conditioned media compared with that in unconditioned media (155.00 (10.00) pg/µg v 1.434 (0.695) pg/µg) was found. The effect of CEC-conditioned media on CLPF IL8 secretion was NF-κB dependent. A protein or DNA array confirmed the involvement of NF-κB and activator protein-1. Purification of a candidate band isolated with the use of sodium dodecyl sulphate-polyacrylamide gel electrophoresis and subsequent sequencing showed soluble galectin-3 to be a strong CLPF-activating factor. Depletion of galectin-3 from conditioned media by immunoprecipitation abolished the CLPF stimulatory effect. Conclusions: Using a classical biochemical approach, soluble galectin-3 was identified as a strong activator of CLPFs produced by CEC. Galectin-3 induced NF-κB activation and IL8 secretion in these cells and may be a target for future therapeutic approaches to reduce or avoid stricture formation.